Assessment of climate change in the North-East Region of Côte d'Ivoire: future precipitation, temperature, and meteorological drought using CMIP6 models - Kouman, K. D.; Akpoti, Komlavi; Kouadio, B. H.; Kabo-bah, A. T.; Dembélé, Moctar; Siabi, E. K.; Mensah, J. K. (Informa UK Limited, 2024)
Climate change effects are expected to be profoundly local and region-specific, underlining the urgent need for local-level assessments. This study emphasizes the agriculturally important Zanzan region of northeastern Côte d'Ivoire and examines future changes in precipitation, temperature, and resultant drought conditions based on six global climate models (GCMs) from the Coupled Model Intercomparison Project 6 (CMIP6) under shared socioeconomic pathways (SSPs) scenarios - SSP2-4.5 and SSP5-8.5. We integrate data from 12 stations within the Zanzan region, applying CMhyd software to correct model biases. Key statistical metrics confirm the well-calibrated nature of the corrected GCMs vis-a-vis observed data. Projections show a decrease in annual precipitation by an average of 133 mm and 177 mm under SSP2-4.5 and SSP5-8.5 scenarios respectively by 2100. Future precipitation patterns suggest a shift towards the prevalent dry season. Tmax and Tmin are projected to increase by þ3 C and þ4.8 C (SSP2-4.5 and SSP5-8.5) and þ3.3 C (both scenarios) respectively, by the end of the century. These changes suggest an intensification of severe droughts, particularly in the 2050s and 2080s, as assessed by the SPEI. Additionally, extreme temperatures (TX90p) and consecutive dry days (CDD) are projected to intensify, posing imminent threats to food security, water resources, and public health in the Zanzan region. This study bridges a critical gap by offering localized insights into future climate scenarios, thereby enhancing our understanding of the region-specific impacts of climate change. The research also underscores the urgency of adaptation and mitigation strategies tailored to the Zanzan region’s vulnerabilities.